TCR-Induced Tyrosine Phosphorylation at Tyr270 of SUMO Protease SENP1 by Lck Modulates SENP1 Enzyme Activity and Specificity - Li, Yun-Yi; Cen, Haohua; Gong, Bei-Ni; Mai, Siqi; Wang, Qi-Long; Mou, Sisi; Li, Yingqiu (Frontiers in Cell and Developmental Biology, 2022)
SUMO (small ubiquitin-like modifier) modification plays an important regulatory role in TCR signaling transduction. SUMO-specific proteases (SENPs) have dual enzyme activities, they can both process SUMO precursors as endopeptidases and participate in SUMO deconjugation as isopeptidases. It remains unclear how SUMO system, especially SENP1, is regulated by TCR signaling. Here, we show that Lck phosphorylates tyrosine 270 (Y270) of SENP1 upon TCR stimulation, indicating that SENP1 is a substrate of Lck. In vitro endopeptidase activity analysis showed that either mutating SENP1 Y270 to phenylalanine (F) to mimic the phosphorylation-defective state or to glutamate (E) to mimic the negative charge of tyrosine phosphorylation in the enzyme microenvironment, did not change its endopeptidase activity towards pre-SUMO1. However, SENP1 Y270E but not Y270F mutation　exhibited decreased endopeptidase activity towards pre-SUMO3. Through in vivo isopeptidase activity analysis by rescue expression of SENP1 and its Y270 mutants in a SENP1 CRISPR knockout T cell line, we found that SENP1 Y270F downregulated its isopeptidase activity towards both SUMO1 and SUMO2/3 conjugation by reducing SENP1 binding with sumoylated targets. While overexpression of SENP1 inhibited TCR-induced IL-2 production, overexpression of SENP1 Y270F enhanced it instead. In summary, TCR-induced Y270 phosphorylation of SENP1 may promote its isopeptidase activity, and specifically decrease its endopeptidase activity against pre-SUMO3, which finely tunes activation of T cells.